صعوبات تطبيق التقويم المستمر في التعليم الابتدائي من وجهة نظر الأساتذة - فارح, عبد اللطيف; طعبلي, محمد الطاهر (جامعة الوادي University of Eloued, 2018)
هدفت هذه الدراسة، إلى التعرف على الصعوبات التي تعيق تطبيق التقويم المستمر، في ضوء المناهج المعاد كتابتها في المرحلة الابتدائية، من وجهة نظر الأساتذة، باعتبارهم المنفذين للمناهج؛ و قد اعتمدت الدراسة على المنهج الوصفي التحليلي، باستخدام أربعة مقاييس، تم تطبيقها على عينة من أساتذة التعليم الابتدائي، قوامها 290 أستاذا و أستاذة، تم اختيارهم بطريقة العينة العشوائية الطبقية. توصلت الدراسة إلى جملة من النتائج أهمها أن صعوبة تطبيق التقويم المستمر في التعليم الابتدائي تتمثل في الاكتظاظ و استخدام أساليب متعددة، بينما كان استخدام الشبكات و التكوين الأقل صعوبة من وجهة نظر الأساتذة.ABSTRACT: the present study aimed to identify the difficulties that hinder the application of continuous assessment in the light of the rewritten curricula in the primary stage from the teachers point of view as they are implementers of the curricula. This study was based on a descriptive analytical approach, using four tests applied to a sample of teachers of primary education consisting of 290 teachers of both sexes. They were selected in a stratified random sampling method. The present study found several results, among which the most important was that the difficulty of applying the continuous assessment in primary education is related to the overcrowding and the use of multiple methods, while using of networks was of less difficulty degree according to them.
مقال
Keywords: التقويم المستمر؛ صعوبات؛ التعليم الابتدائي؛ الأساتذة; continuous assessment; difficulties; primary stage; teachers.